2017
DOI: 10.1088/1742-6596/807/5/052011
|View full text |Cite
|
Sign up to set email alerts
|

A note on the upper critical field of Sr2RuO4 under strain

Abstract: In the light of the recently discussed mechanism for suppression of superconductivity in multi-orbital systems called inter-orbital effect, here we extend our analysis of the upper critical field in Sr2RuO4 now under strain. We show that the presence of the standard orbital effect and the new mechanism can consistently account for the qualitative changes observed in the upper critical field for the strained system, in particular, combining the overall enhancement of the critical field with the reduction in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Studies of the upper critical field [22][23][24][25][26][27] revealed another serious discrepancy. At low temperatures, a first-order superconducting to normal transition in the magnetocaloric effect 26 , the specific heat 25 and magnetization 27 was observed under a magnetic field applied in the x-y plane, characteristic of Pauli-limiting 28,29 and inconsistent with the Knight shift measurements. For about 20 years there have been a number of attempts to resolve this puzzling behaviour with little or no success.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies of the upper critical field [22][23][24][25][26][27] revealed another serious discrepancy. At low temperatures, a first-order superconducting to normal transition in the magnetocaloric effect 26 , the specific heat 25 and magnetization 27 was observed under a magnetic field applied in the x-y plane, characteristic of Pauli-limiting 28,29 and inconsistent with the Knight shift measurements. For about 20 years there have been a number of attempts to resolve this puzzling behaviour with little or no success.…”
Section: Introductionmentioning
confidence: 83%
“…The first order transition is characteristic of Pauli limiting or spin limiting 28,29 , also known as Chandrasekhar-Clogston limit 47,48 . The paramagnetic suppression of superconductivity takes place due to the magnetic field lifting the degeneracy of electronic states with opposite momenta k and −k that form the Cooper pair.…”
Section: A Gap-function and Phase Diagrammentioning
confidence: 99%
“…For the temperature dependence we use the approximate weak coupling expression, 56 ∆ 0 (t) = ∆ 0 (0) tanh 1. 78 1…”
Section: Iv1 Superconducting Gap Structurementioning
confidence: 99%
“…These equations indicate that there can be nodes in the superconducting spectrum of Sr 2 RuO 4 given the nontrivial form factors originated from the normal-state Hamiltonian Ĥ0 (k), even though the gap in the orbital basis is isotropic (s-wave). Note that the fitness function FC (k) appears in this context as a key parameter defining the nodes, reinforcing its importance for the understanding of the phenomenology of superconducting states in complex materials [15,16,17,18,19,12]. As a final note, keeping higher order terms in ∆ 2 0 in the expansion above, we find structures associated with Bogoliubov Fermi surfaces, which can be understood as inflated nodes [20,21].…”
Section: Origin Of Line Nodesmentioning
confidence: 62%